Analisis pengalokasian dan penyajian environmental cost pada Rumah Sakit Umum Monompia GMIBM Kotamobagu - Kereh, Keiko Takeshi Dionisius; Saerang, David Paul Elia; Rondonuwu , Sintje (Manajemen Bisnis dan Keuangan Korporat, 2025)
The objective of this study is to analyse the allocation and presentation of environmental costs at Monompia GMIBM General Hospital, Kotamobagu. The research employs a descriptive qualitative method, with data obtained through interviews and document analysis. The results are clear: the allocation of environmental costs has not been implemented systematically. Recognition and measurement of costs are based on the benefits received and previous budget realizations. However, they do not fully comply with applicable accounting standards. It is clear that the presentation and disclosure of environmental costs in the financial statements is limited and not explicitly classified. The study's clear recommendation is a more structured implementation of environmental accounting practices. This will improve accountability and transparency in the hospital's environmental management.